مجموعة دول البريكس: بين تحديات النظام متعدد الأقطاب وهدف تعديل الاقتصاد العالمي BRICS countries: between the challenges of the multipolar system and the goal of adjusting the global economy - ناصري, سميرة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
تعالج مداخلتنا هذه تداعيات صعود دول البريكس على هيكل وبنية النظام الاقتصادي العالمي وما قد يصاحب ذلك من تحول في موازين القوى، فدراسة إرهاصات ظهور هذا التكتل، أهدافه وتطوره تشير لانتقال الثقل الاقتصادي للهيمنة الأحادية الغربية(الأمريكية والأوروبية) بعد الأزمة المالية العالمية سنة2008 للقوى الصاعدة التي تسعى لإدخال إصلاحات جذرية تمنع تحكم الولايات المتحدة بالاقتصاد العالمي، من ناحية أخرى فان تدخل دول المجموعة للعب ادوار مهمة في إدارة الملفات الأمنية والاهتمام بقضايا السياسة العالمية أصبح يشكل تهديدا على المكانة السياسة لتلك القوى. الكلمات المفتاحية: دول البريكس، نظام متعدد الأقطاب، الهيمنة الاقتصادية الغربية، تعديل الاقتصاد العالمي. Abstract: The implications of the emergence of the BRICS States on the structure of the world economic system and the accompanying changes in the balance of power. The study of the implications of the emergence of this bloc, its objectives and development indicate the transfer of economic weight to the unilateral Western (American and European) domination after the global financial crisis in 2008 To introduce radical reforms that prevent US control of the global economy, on the other hand, the intervention of the countries of the group to play important roles in the management of security files and attention to issues of global policy has become a threat to the political status of those forces Keywords: BRICS States, a multipolar system, Western economic hegemony, the adjustment of the global economy